An improvement of H. Wang preconditioner for L-matrices - Nasabzadeh, Hamideh (International Journal of Applied Mathematical Research, 2016)
In this paper, we improve the preconditioner, that introduced by H. Wang et al [6]. The H. Wang preconditioner \(P\in R^{n× n}\) has only one non-zero, non-diagonal element in \(P_{n1}\) or \(P_{1n}\) , when \(a_{1n}a_{n1} e 0\) . But the new preconditioner has only one non-zero, non-diagonal element in \(P_{ij}\) or \(P_{ji}\) if \(a_{ij}a_{ji} e 0\), so the H. Wang preconditioner is a spacial case of the new preconditioner for L-matrices. Also we present two models to construct a better \(I+S\) type preconditioner for the \(AOR\) iterative method. Convergence analysis are given, numerical results are presented which show the effectiveness of the new preconditioners.